PERCEIVED INFLUENCE OF AUGMENTED REALITY ON THE LEARNING OF CHEMISTRY OSOGBO LOCAL GOVERNMENT AREA, OSUN STATE, NIGERIA. - ABANIKANNDA, Mutahir; Aderinto, Grace Anu (Chemistry in Education, 2024)
Augmented reality (AR) technology is becoming increasingly prevalent in chemistry education. AR is regarded as an essential pedagogical resource that facilitates the comprehension of complex concepts at all educational levels. Despite the numerous reported advantages of AR in education, research is yet to be conducted on the influence of AR on secondary school chemistry education in the Nigerian state of Osun. Thus, this study was conducted to determine the impact of an AR system used to teach secondary school pupils about material structures and chemical equilibrium on their motivation, cognitive burden, and technology acceptance. Material structures and chemical equilibrium is an essential subtopic in chemistry education, particularly for high school students; however, this can be difficult to grasp as it is abstract. Augmented Reality (AR) technology, considered an added value compared to traditional learning materials such as textbooks, two-dimensional images, and video, is one way to facilitate this learning process.  A class of 14- to 16-year-old (eleventh-grade) students in the Osogbo Local Area of Osun State, Nigeria, evaluated the impact of augmented reality on chemistry learning. This study employed a mixed-methods survey research design with an ex-post facto methodology. Twenty secondary institutions in Osogbo Local Government will be chosen using a simple random sampling technique, yielding 300 pupils. The data were collected using an achievement test, a cognitive burden scale, and a semi-structured interview form. After analyzing the results, we can conclude that these students favorably viewed this augmented reality (AR) application in the learning process. Numerous students need help to comprehend chemistry's symbolic and molecular representations. This may have enhanced their comprehension of chemical symbols and concepts. In addition, the results indicate that computerized models can serve as a means for students to generate mental images.